New syllabus primary Mathematics workbook 5A - Yee , Foong Pui; Brandon Oh; Lim Li Gek Pearlyn (Karachi : Oxford university press, 2019)
The "Primary Mathematics Workbook 5A" typically aligns with the curriculum designed for students in their 5th year of primary school. It serves as a supplement to the core textbook, reinforcing key mathematical concepts and providing practice exercises. A general summary of the topics might include: 1-Number Sense and Operations: 2- Geometry: 3- Measurement: 4-Data Handling. 5- Word Problems. 6- Algebraic Thinking
Keywords: Mathematics workbook 5A; Oxford Mathematics workbook 5A